2015
DOI: 10.1007/s10570-015-0774-0
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose/nanoclay composite films with high water vapor resistance and mechanical strength

Abstract: Cellulose based films were fabricated by dissolving the micro-crystalline cellulose and cotton linter in a LiOH/urea aqueous system, followed by regeneration in acetone. The water vapor transmission rate (WVTR) values of the films were measured and the results indicated that regenerated micro-crystalline cellulose (RMCC) showed lower WTVR than regenerated cotton linter (RCL). WVTR values were proportional to the thickness of samples. The films also exhibited high oil resistance as no fat oil could pass through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Fiber strength is generated through hydrogen interchain bonds, which prevent melting. The cellulose structure can absorb a large amount of water, but it cannot dissolve in water [ 23 ]. Because of the existence of hydroxyl structures and a regular structure that leads to the creation of crystalline microfibrils and fibres with strong hydrogen bonds, cellulose is commonly utilised in packaging as paper or cardboard.…”
Section: Bio-based Polymersmentioning
confidence: 99%
“…Fiber strength is generated through hydrogen interchain bonds, which prevent melting. The cellulose structure can absorb a large amount of water, but it cannot dissolve in water [ 23 ]. Because of the existence of hydroxyl structures and a regular structure that leads to the creation of crystalline microfibrils and fibres with strong hydrogen bonds, cellulose is commonly utilised in packaging as paper or cardboard.…”
Section: Bio-based Polymersmentioning
confidence: 99%
“…Generally, layered filler with large aspect ratio can act as impermeable nanoplatelets to intensity the tortuosity of the penetration paths for diffusing molecules. Moreover, it is found that oriented filler from hot pressure drying of RC/nanofiller is an effective method to further prolong paths of gas molecule permeability and finally to improve barrier property . In this work, it shows that the hydrophobicity of oriented filler and interfacial interactions are important factors in determining the water vapor barrier properties of the RC film.…”
Section: Resultsmentioning
confidence: 84%
“…Of note, the gas barrier of these nanocomposites was better than those of commonly used synthetic polymers, like polystyrene, polyethylene, and polypropylene. Farmahini-Farahani et al [ 97 ] used the same solvent used by Wang et al [ 96 ] to prepare cellulose/MMT nanocomposite films and investigated their water-vapor resistance. In this study, Cloisite Na + (Na-MMT) was added to LiOH/urea/ and stirred and filtered before being pre-cooled.…”
Section: Barrier Performancementioning
confidence: 99%